2020
DOI: 10.3390/foods9091173
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral Wheat Types Release Fewer Celiac Disease Related T Cell Epitopes than Common Wheat upon Ex Vivo Human Gastrointestinal Digestion

Abstract: Celiac disease (CeD) is an autoimmune enteropathy triggered by immunogenic gluten peptides released during the gastrointestinal digestion of wheat. Our aim was to identify T cell epitope-containing peptides after ex vivo digestion of ancestral (einkorn, spelt and emmer) and common (hexaploid) wheat (Fram, Bastian, Børsum and Mirakel) using human gastrointestinal juices. Wheat porridge was digested using a static ex vivo model. Peptides released after 240 min of digestion were analyzed by liquid chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Most studies on the safety of cereals in celiac patients investigate the products after peptic–tryptic digestion (PTd) [ 25 ]. The outcomes most frequently considered are: agglutination, the secretion of cytokines or the alteration of transepithelial electrical resistance (TEER) in cell models, such as Caco-2 cells [ 26 , 27 , 28 ], K562 (S) cells [ 26 , 29 ], or gliadin reactive T-cell lines [ 23 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies on the safety of cereals in celiac patients investigate the products after peptic–tryptic digestion (PTd) [ 25 ]. The outcomes most frequently considered are: agglutination, the secretion of cytokines or the alteration of transepithelial electrical resistance (TEER) in cell models, such as Caco-2 cells [ 26 , 27 , 28 ], K562 (S) cells [ 26 , 29 ], or gliadin reactive T-cell lines [ 23 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, no influence on these parameters by environmental factors, such as the harvest year and N fertilization was observed [20,22]. In a study by Asledottir et al (2020) after an ex vivo digestion, the ancestral cereals (T. monococcum, T. aestivum ssp. spelta and T. diccocum) released fewer T-cell epitope-containing peptides than the common wheat varieties [25].…”
Section: Triticum Aestivum Ssp Speltamentioning
confidence: 99%
See 1 more Smart Citation
“…However, detection would require that the patients have maintained a gluten-containing diet until the time of gastroendoscopy. In addition, differences in wheat strains and -gliadin gene content used for food (44), as well as individual variation in ability to proteolytically digest gluten (45), are factors that might underpin the lack of staining in some of the CeD patient samples. mAb 3.C11 specifically inhibited T cell activation and proliferation in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, T. monococcum is only grown in some locations of the Mediterranean area. However, some studies demonstrated that T. monococcum boasts other advantages such as low-immunogenic gluten [3,8], low contents of amylase/trypsin-inhibitors [10], high contents of protein [12], lutein and tocols [4,13,26], carotenoids [2,4], resistant starch [4], polyphenolic antioxidants [16], trace elements (selenium) [16]. Einkorn wholemeal flour is rich in lipids (mostly unsaturated fatty acids) [12,17].…”
Section: Introductionmentioning
confidence: 99%